Emotional Education: The Lost Element of Social Justice - Barrantes-Elizondo, Lena (2016)
This essay aims to demonstrate how social injustice becomes a side effect of the lack of an emotional educational program in the education system. The discussion focuses in the necessity of channeling emotional abilities since early ages and making the four basic dominions of the emotional ability: self-awareness, self-government, social coexistence and relationships management, part of the common knowledge. The emotional ability is a necessary element for both current and future education. This ability is a fundamental piece in the society puzzle, it constitutes a key element in a fair complex human coexistence where individuals learn to govern over their emotions through strategies since their childhood. On the other hand, the need to acquire a deeper knowledge of oneself emotions is highlighted, as well as identifying the emotions of others, develop the ability to regulate our own negative emotions, the ability to create positive emotions and the ability to self motivate in order to adopt a positive attitude towards life. Among the main conclusions, these can be cited: the socio-emotional abilities become a basic aspect of human development; an educational program that seeks to approach this ability requires more than a list of values and attitudes; in order to get out of this a systematic answer, clearly set objectives, contents, mediating activities and evaluation strategies are required.